GENDER EQUALITY IMPACT ANALYSIS ON ACADEMIC OF SINGLE PARENTS CHILREN - Pratiwi, Alifah Indah (Spektrum Analisis Kebijakan Pendidikan, 2021)
This study aims to describe the application of gender equality in single parent families in the Spinmotion Yogyakarta community and the impact of gender equality on the academic achievement of children in the Spinmotion Yogyakarta community. Descriptive qualitative research, conducted in the Special Region of Yogyakarta. The research subjects are single parents who are members of the Yogyakarta Spinmotion community. Data collection techniques used are observation, interviews, and documentation. The data were analyzed from the informant's point of view with data collection techniques, data condensation, data presentation, and drawing conclusions. The validity of the data was tested by triangulation of sources and increasing persistence. The results of this study: (1) The theoretical meaning of gender is still understood as a gender difference but in the application of gender roles and work it does not refer to gender. The single parent family of the Spinmotion Yogyakarta community has implemented gender equality for their children. (2) Most of the single parent children who are members of the Yogyakarta Spinmotion community have not experienced any changes in learning at school, especially in academic achievement.Keywords: Gender Analysis, Gender Equality, Single Parents,Academic Achievement